Pengalaman Pasien ODHA dalam Adaptasi Fisiologis - Juli Andri; Agus Ramon; Padila Padila; Andry Sartika; Eka Putriana (Journal of Telenursing (JOTING), 2020)
This study aims to explore the experiences of ODHA patients in physiological adaptations in Dr. M. Yunus Bengkulu. This type of research is qualitative research with survey methods and in-depth interviews (In-depth Interview). The results showed that the knowledge aspect of the three informants understood and knew about HIV / AIDS. Elements of the problem of physiological adaptation are obtained in the form of continuous diarrhea, continued appetite, drastic weight loss, fatigue when on the move, insomnia or sleep disturbances, itchy skin, infection of the skin, uncomplicated illness (fever, flu, and cough), joint pains, tingling sensation, forgetfulness, low vision, and refusing to open up to the surrounding environment. The aspect of ODHA experience in overcoming the problem of physiological adaptation is that ODHA not only depends on ARV drugs, but they use other medications according to complaints and use herbal medicines. In conclusion, the three informants understand HIV / AIDS, have many problems that arise in physiological adaptation, and how ODHA to overcome the problem of physiological adaptation, namely traditional and pharmacological ways. Keywords: Physiological Adaptation, Experience of ODHA